2021
DOI: 10.1186/s12882-021-02267-4
|View full text |Cite
|
Sign up to set email alerts
|

Low plasma magnesium concentration and future abdominal aortic calcifications in moderate chronic kidney disease

Abstract: Background Higher plasma magnesium concentrations are associated with reduced cardiovascular disease risk in chronic kidney disease (CKD) patients. The importance of plasma magnesium concentration for vascular calcification in earlier stages of CKD remains underexplored. This study investigated whether plasma magnesium is a determinant for the presence and severity of vascular calcification in moderate CKD. Methods Retrospective analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…found that higher serum magnesium levels were significantly associated with lower abdominal aortic calcification volume in ESKD patients [ 26 ]. Observational studies on dialysis patients have shown that higher blood magnesium concentration is associated with a lower risk of vascular calcification [ 27 , 28 ]. Both in vitro and in vivo models have demonstrated that magnesium can prevent the transdifferentiation of osteoblastic vascular smooth muscle cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…found that higher serum magnesium levels were significantly associated with lower abdominal aortic calcification volume in ESKD patients [ 26 ]. Observational studies on dialysis patients have shown that higher blood magnesium concentration is associated with a lower risk of vascular calcification [ 27 , 28 ]. Both in vitro and in vivo models have demonstrated that magnesium can prevent the transdifferentiation of osteoblastic vascular smooth muscle cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low serum Mg was found associated with the prevalence and incidence of aortic valve calcification in an adult population without known CVD and CKD [ 44 ]. In moderate CKD, low serum Mg was associated with abdominal aortic calcification, increased pulse pressure, mitral valve calcification and increased intima media thickness [ 45 , 46 , 47 ]. The findings that decreased levels of GRP and Mg and increased levels of P are independent and cumulative risk factors of VC, are in line with the current knowledge of their involvement on the pathophysiological mechanisms of cardiovascular calcification, and reinforce the crucial role of bone mineral metabolism in cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding all these risk factors created in the context of CKD, hypomagnesemia is yet another interesting and underappreciated risk factor for cardiovascular mortality. Observational data have shown an association between low serum magnesium concentrations or magnesium intake and the increased risk of atherosclerosis, coronary artery disease, arrhythmias, aortic valve calcification [ 47 , 48 , 49 , 50 ], and heart failure [ 51 ]. Furthermore, low serum magnesium levels were associated with an increased risk of end-stage renal disease associated with high serum phosphate levels in a cohort study, suggesting a strong relationship between magnesium deficiency and the adverse effects of high phosphate levels.…”
Section: Cardiovascular Mortality In Chronic Kidney Diseasementioning
confidence: 99%